Redescription of Leiocapitella atlantica Hartman, 1965 and description of a new species from the Southeast Brazil (Annelida, Capitellidae) - Da Silva, Camila Fernanda; Amaral, Antonia Cecilia Zacagnini (Zootaxa, 2020)
The genus Leiocapitella was described as having a wide variation on the number of thoracic chaetigers (13–17); however, this variation was added to the diagnosis of the genus based on undescribed species. A shortening in the range of variation of thoracic chaetigers is proposed until a re-examination of these species and a formal description be made. Currently, there are five valid species and a single species has been previously recorded in Brazil. The aim of this study was to investigate the diversity of this genus occurring in the Southeast Brazil. A new species has been found in samples collected on subtidal areas, Leiocapitella sensibilis sp. nov., and it is described and compared to other species of the genus. Leiocapitella atlantica Hartman, 1965 is redescribed after examination of the type material.